POLITIK PENGAWASAN DPRD DALAM UPAYA PEMAKZULAN KEPALA DAERAH : Studi Kasus Wali kota Surabaya - Amalia, Luky Sandra (Jurnal Penelitian Politik, 2025)
Impeachment as apublic officialproceedings conducted byparliament has become a quitepopular discourse lately despite the impeachment efforts that occurred over many issues associated with interparty rivalry rather than as a process ofparliamentary oversight Impeachment in the context oflndonesian politics under the existing constitution can only be carried by the House ofRepresentatives against the President Vice President on the basis ofcertain reasons such as violation of law national treason corruption and others The impeachment which is carried by District Legislative Council of Surabaya against the local mayor can be an interesting case because of besides there is no legal basis under the constitution the process becomes a new precedent in the political dv namics of the local parliament This paper attempts to explore the District Legislative Council impeachment case comprehensively The case is to be analyzedfrom aspect of regulation and process as well as political motives behind the impeachment effort This paper will also unravel the dynamics that occur in the impeachment process and its impact on parliamentary politics at the local level